Laminoplasty and In‐Site Regrafting for the Treatment of Thoracic Ossification of the Ligamentum Flavum: A Surgical Technique - Hu Qian; Xiuqian Wang; Ting Lei; Jun Ao; Jianpu Qin (Orthopaedic Surgery)
ABSTRACT Objective Current surgical strategies for thoracic ossification of the ligamentum flavum (TOLF) are denounced by thoracic kyphosis, loss of spinal motion range, etc. A new surgical technique, laminoplasty and in‐site regrafting (LPIR), was modified to address the problems. This study aimed to report the safety and feasibility of LPIR for TOLF treatment. Methods This retrospective study reported the outcome of eight consecutive patients (3 males and 5 females, mean age 52.87 years) with TOLF who underwent LPIR surgery from January 2019 to March 2024. Pre‐ and post‐operative data including x‐ray, computerized tomography (CT), magnetic resonance imaging (MRI), the modified Japanese Orthopedic Association score (mJOA), the visual analog scale (VAS), and complications were collected to evaluate the outcome. Results All surgeries were performed successfully, significantly alleviating symptoms postoperatively. During an average follow‐up period of 28.63 months, the VAS score reduced from 4.50 ± 1.00 pre‐operatively to 1.63 ± 0.48 on the third post‐operative day and further reduced to 0.50 ± 0.70 during the last follow‐up. The mJOA score increased from 3.63 ± 0.70 pre‐operatively to 6.13 ± 0.78 on the third postoperative day and further increased to 8.88 ± 1.27 during the last follow‐up. No severe complications were observed. Conclusions LPIR exhibited significant safety and feasibility for treating TOLF, offering a novel strategy for managing this problem.